2023
DOI: 10.1002/ajmg.a.63246
|View full text |Cite
|
Sign up to set email alerts
|

CHST3‐related skeletal dysplasia in 14 patients: Identification of 8 novel variants and further expansion of the phenotypic spectrum

Abstract: Biallelic variants in CHST3 gene result in congenital dislocation of large joints, club feet, short stature, rhizomelia, kypho-scoliosis, platyspondyly, epiphyseal dysplasia, flared metaphysis, in addition to minor cardiac lesions and hearing loss. Herein, we describe 14 new patients from 11 unrelated Egyptian families with CHST3-related skeletal dysplasia. All patients had spondyloepiphyseal changes that were progressive with age in addition to bifid distal ends of humeri which can be considered a diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…None of the patients had hearing loss. Seven patients reported in this study had supernumerary carpal ossification centers which were observed in only six previously reported patients and most of them were above 10 years of age (Albuz et al, 2020;Otaify et al, 2023;Tuysuz et al, 2009;van Roij et al, 2008). The other two affected individuals were of ages 3 and 6 years, suggesting the possibility of observing this feature later in life.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…None of the patients had hearing loss. Seven patients reported in this study had supernumerary carpal ossification centers which were observed in only six previously reported patients and most of them were above 10 years of age (Albuz et al, 2020;Otaify et al, 2023;Tuysuz et al, 2009;van Roij et al, 2008). The other two affected individuals were of ages 3 and 6 years, suggesting the possibility of observing this feature later in life.…”
Section: Discussionmentioning
confidence: 52%
“…It appears that mitral, tricuspid, and aortic valves are commonly affected in that order with thickened leaflets, stenosis, and insufficiency. In recent study by Otaify et al, severe cardiac valvular insufficiencies were reported in three individuals (Otaify et al, 2023). Considering this observation, a cardiac evaluation is warranted in patients with CHST3 deficiency.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations